2020
DOI: 10.1097/mlr.0000000000001405
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2 Testing in Massachusetts Among Women With Private Insurance or Medicaid, 2011–2015

Abstract: Purpose: Testing for BRCA1/2 mutations has increased among privately insured women in the United States. However, little is known about testing rates or trends among women with Medicaid. We sought to determine whether BRCA1/2 testing rates differed between women with private insurance compared with women with Medicaid in a state where both insurance types cover the test, and to compare testing trends from 2011 to 2015. Methods: We conducted a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Rhode Island’s Medicaid program focuses on BRCA coverage only for those in its managed care programs. A 2020 analysis of an all-payer claims database in Massachusetts noted an increase in mean monthly BRCA1/2 tests per 100,000 Medicaid-insured women from 3.7 in 2011 to 14.7 in 2015 [ 51 ]. On average, BRCA1/2 testing rates increased at a similar rate for both privately and Medicaid-insured women.…”
Section: Resultsmentioning
confidence: 99%
“…Rhode Island’s Medicaid program focuses on BRCA coverage only for those in its managed care programs. A 2020 analysis of an all-payer claims database in Massachusetts noted an increase in mean monthly BRCA1/2 tests per 100,000 Medicaid-insured women from 3.7 in 2011 to 14.7 in 2015 [ 51 ]. On average, BRCA1/2 testing rates increased at a similar rate for both privately and Medicaid-insured women.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, Knerr et al reported a 33% increase in BRCA testing from 2005 to 2015 in women over 18 without an incident breast or ovarian cancer within their hospital system in Washington state [ 13 ]. Pace et al reported that in Massachusetts, the mean monthly number of tests per 100,000 women doubled to quadrupled from 2011 to 2015, depending on the type of insurance [ 14 ]. However, the absolute rates of testing for HCS in Arkansas remained low.…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate exploratory models that controlled for key demographic differences, those with state employee coverage were 1.6 to 4.5 times more likely to receive genetic testing compared to commercial enrollees, while commercial enrollees were substantially more likely to receive any type of genetic testing than Medicaid enrollees. Type of coverage played a similarly important role in a study more narrowly focused on women receiving BRCA1/2 testing in Massachusetts; testing among privately insured women increased from 9.3 in 2011 to 18.4 in 2015, while among Medicaid enrollees, it increased from 3.7 in 2011 to 14.7 in 2015 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%